This action might not be possible to undo. Are you sure you want to continue?

Welcome to Scribd! Start your free trial and access books, documents and more.Find out more

Kanak Kshetri

1

**Introduction: Why Predicates Logic
**

• Want to make the statement that everything has a certain property – e.g. “All men are mortal” • Propositional Logic doesn’t provide us any structure to express this – e.g. could say “P = all men are mortal” – but P is atomic, and we can’t make any use of the fact that the property is supposed to hold everywhere • Predicate Logic is propositional logic with quantiﬁers

2

2.1

**Language of Predicate Logic
**

Predicates

• A statement that an object has a property – e.g. x is even • We write predicate names with capital letters and variables in lowercase – e.g. F (x)

2.1.1

Deﬁnition: Predicate

• Any term in the form F (x), where F is a predicate name and x is a variable name is a well formed formula • Similarly, F (x1 , x2 , · · · , xk ) is a well formed formula and represents a predicate with k variables 2.1.2 Deﬁnition: Universe

• Deﬁnes the set of values that variables can have • e.g. for “x is even”, we can deﬁne the universe as the natural numbers • Universe usually written U 1

2.2

2.2.1

Quantiﬁers

Deﬁnition: Universal Quantiﬁcation ∀

• Suppose F (x) is a WFF involving the variable x • Then, ∀x.F (x) is a WFF called universal quantiﬁcation • It says that every item in the universe has the property F 2.2.2 Examples of Universal Quantiﬁcation

• ∀x.E(x), U = {x ∈ N|even(x)} where E(x) means x is even – This says that every item in the set of even natural numbers is even. – It is true. • ∀x ∈ N.E(x) – This says that every natural number is even. – It is false. Counterexample: 1 2.2.3 Deﬁnition: Existential Quantiﬁcation ∃

• Suppose F (x) is a WFF involving the variable x • Then, ∃x.F (x) is a WFF called existential quantiﬁcation • It says that at least one item in the universe has the property. 2.2.4 Examples of Existential Quantiﬁcation

• ∃x ∈ N.2 ∗ x = 6 – Says that there is a natural number which when multiplied by 2 gives 6. – This is true (x = 3) • ∃x ∈ Q.x ∗ x = 2 – Says that there is a rational number which when multiplied by itself gives 2 √ – This is false ( 2 is irrational) 2.2.5 Nesting Quantiﬁers

• Want to say: for every integer, there is another one that is larger • ∀x ∈ Z, ∃y ∈ Z, x < y • Note that order is signiﬁcant • ∃x ∈ Z, ∀y ∈ Z, x < y says that there is an integer that is smaller than every other integer. This is false. 2

2.3

2.3.1

**Expanding Quantiﬁed Expressions
**

Expansions

• ∀x.F (x) = F (c1 ) ∧ F (c2 ) ∧ · · · ∧ F (cn ) • ∃x.F (x) = F (c1 ) ∨ F (c2 ) ∨ · · · ∨ F (cn ) 2.3.2 Exercise 1

• U = {1, 2, 3} • Remove the quantiﬁers in the following • ∀x.F (x) – F (1) ∧ F (2) ∧ F (3) • ∃x.F (x) – F (1) ∨ F (2) ∨ F (3) • ∃x.∀y.G(x, y) – (G(1, 1) ∧ G(1, 2) ∧ G(1, 3)) ∨ (G(2, 1) ∧ G(2, 2) ∧ G(2, 3)) ∨ (G(3, 1) ∧ G(3, 2) ∧ G(3, 3)) 2.3.3 Exercise 2

• U =Z • Expand: ∀x ∈ {1, 2, 3, 4}.∃y ∈ {5, 6}.F (x, y) • (F (1, 5) ∨ F (1, 6)) ∧ (F (2, 5), F (2, 6)) ∧ (F (3, 5), F (3, 6)) ∧ (F (4, 5) ∨ F (4, 6))

2.4

Scope of Variable Bindings

• Use parentheses to clarify scope • Assume smallest scope is smallest subexpression otherwise

2.5

2.5.1

**Translating Between English and Logic
**

Example: "Some birds can ﬂy"

• Assume universe is all animals • B(x) is true if x is a bird • F (x) is true if x can ﬂy • Then, ∃x.B(x) ∧ F (x) expresses “some birds can ﬂy” • NOTE: ∃x.B(x) ⇒ F (x) is wrong 3

– If B(x) is false, then the implication is true – Then, if x is a horse, the implication is true – Suppose all the birds in the universe can’t actually ﬂy – Since we’ve found something that makes the implication true, by existential quantiﬁcation, the implication is true – This is a contradiction 2.5.2 Exercise 3: Express the statements formally

• Given: E(x) means x is even, O(x) means x is odd, Universe is natural numbers • There is an even number. – ∃x.E(x) • Every number is either even or odd. – ∀x.E(x) ∨ O(x) • No number is both even and odd. – ∀x.¬(E(x) ∧ O(x)) • Sum of two odd numbers is even – ∀x, y.O(x) ∧ O(y) ⇒ E(x + y) • Sum of an odd number and an even number is odd – ∀x, y.O(x) ∧ E(y) ⇒ O(x + y) • We don’t have the same bug as “some birds can ﬂy” with the implication because we’re doing a universal quantiﬁcation and not an existential one. So, if there is a single pair of odd numbers whose sum is not even, the implication would be false, which is what we want. 2.5.3 Exercise 4: Animal Logic 193

• Given: predicates for Bird, Dove, Chicken, Pig, Fly, Wings, M (x, y) means x has more feathers than y • Chickens are bird – ∀x.C(x) ⇒ B(x) • Some doves can ﬂy – ∃x.D(x) ∧ F (x) • Pigs are not birds 4

– ∀x.P (x) ⇒ ¬B(x) • Some birds can ﬂy, some can’t – ∃x.B(x) ∧ F (x) • An animal needs wings in order to ﬂy – ∀x.F (x) ⇒ W (x) • If a chicken can ﬂy, then pigs have wings – ∃x, ∀y.(C(x) ∧ F (x)) ⇒ (P (y) ∧ W (y)) • Chickens have more feathers than pigs do. – ∀x, ∀y.C(x) ∧ P (y) ∧ M (x, y) • An animal with more feathers than any chicken can ﬂy. – ∀x, ∀y.C(y) ∧ M (x, y) ⇒ F (x) 2.5.4 Exercise 5: Back to english

• ∀x.(∃y.wantsT oDanceW ith(x, y) – everyone has someone they would like to dance with • ∃x.(∀y.wantsT oP hone(y, x)) – everyone has someone they would like to phone • $∃ x. (tired(x) ∧ ∀ y. helpsMoveHouse(x,y)) – there is someone who will help anyone move despite being tired

3

**Computing with Quantiﬁers
**

• Predicate is just a function that returns a boolean • Quantiﬁers built into haskell – all : a -> Bool -> [a] -> Bool – any : a -> Bool -> [a] -> Bool – and : [Bool] -> Bool – or : [Bool] -> Bool

5

3.1

Exercise 6: Haskell expression to Logic, compute value

• Note: using haskell’s builtin functions instead of equivalent Stdm ones • all (== 2) [1,2,3] – ∀x ∈ {1, 2, 3}.x = 2 – False: counterexample is ‘1’ • all (< 4) [1,2,3] – ∀x ∈ {1, 2, 3}.x < 4 – True

3.2

Exercise 7: Haskell expressions to Logic, compute values

• any (== 2) [0,1,2] – ∃x ∈ {1, 2, 3}.x = 2 – True • any (> 5) [1,2,3] – ∃x ∈ {1, 2, 3}.x > 5 – False

3.3

Example 7: ∀x ∈ {1, 2

. (∃y ∈ {1, 2}.x = y) • Convert to haskell • every (\ x -> any (== x) [1,2]) [1,2] – (any (== 1) [1,2]) && every (\ x -> any (== x) [1,2]) [ 2] – ((== 1) 1 || any (== 1) [ 2]) every ( x -> (== x) [1,2]) [ 2] – (True || any (== 1) [ 2]) every ( x -> (== x) [1,2]) [ 2] – True && every (\ x -> (== x) [1,2]) [ 2] – every ( x -> (== x) [1,2]) [ 2] – True && every (\ x -> (== x) [1,2]) [] – True

6

3.4

Exercise 8: Calculate values of expressions

• pxy means x = y + 1 • U = {1, 2} • ∀x.(∃y.p(x, y)) – (∃y.p(1, y)) ∧ (∃y.p(2, y)) (by removing forall) – (p(1, 1) ∨ p(1, 2)) ∧ (p(2, 1) ∨ p(2, 2) (by removing exists) – (F alse ∨ F alse) ∧ (T rue ∨ F alse) – F alse ∧ T rue – F alse – (Haskell veriﬁcation: all (\ x -> any (p x) [1,2]) [1,2] gives False) • ∃x, y.p(x, y) – (∃x.∃yp(x, y) – ((∃y.p(1, y)) ∨ (∃x.p(2, y)) (by removing exists x) – ((p(1, 1) ∨ p(1, 2)) ∨ (p(2, 1) ∨ p(2, 2)) – Since p(2, 1) is true, the whole expression is True – (Haskell veriﬁcation: any (\ x -> any (p x) [1,2]) [1,2] gives True) • ∃x.(∀y.p(x, y)) – (∀y.p(1, y)) ∧ (∀y.p(2, y)) (by removing exists) – (p(1, 1) ∨ p(2, 1)) ∧ (p(1, 2) ∨ p(2, 2)) (by removing forall) – (F alse ∨ T rue) ∧ (F alse ∨ F alse) – T rue ∧ F alse – (haskell veriﬁcation: any (\ x -> all (p x) [1,2]) [1,2] gives False) • ∀x, y.p(x, y) – (∀y.p(1, y)) ∧ (∀y.p(2, y)) (removing forall) – (p(1, 1) ∧ p(1, 2)) ∧ (p(2, 1) ∧ p(2, 2)) (removing forall) – Since p(1, 1) is false, the whole thing becomes false – (haskell veriﬁcation: all (\ x -> all (p x) [1,2]) [1,2] gives False)

4

4.1

**Logical Inference with Predicates
**

Introduction

• Can view inference rules of predicate logic as generalizations of rules from propositional logic 7

• If universe is ﬁnite, then the rules might not be necessary – e.g. ∀x.F (x) could be replaced by F (x1 ), · · · F (xn ), n is the size of the universe – But, propositional inference rules allow us to do deductions when the universe is inﬁnite • Assume universe is nonempty – e.g. forall elimination is invalid when the universe is empty

4.2

Universal Introduction

• If you can prove an element about an arbitrary element of the universe, you have a statement about all elements of the universe. 4.2.1 Append Example

• Deﬁnition ( + + ) : : [ a ] −> [ a ] −> [ a ] [ ] ++ ys = ys ( x : xs ) ++ ys = x : ( xs ++ ys ) • Theorem: Letx :: a, xs :: [a].T hen, x : xs = [x] + +xs – Proof follows directly from the deﬁnition of append – RHS = [x] ++ xs = x : xs = LHS • Theorem: ∀x :: a.∀xs :: [a].x : xs = [x] + +xs – This theorem makes the same claim as the previous – Style is diﬀerent: ∗ Previous one talked about arbitrary elements from the universe ∗ This makes claim about all elements in the universe 4.2.2 Universal Introduction Deﬁnition ∀x.F (x)

• F (x), xarbitrary 4.2.3 Example:

∀x.E(x) ⇒ (E(x) ∨ ¬E(x))

• Proof Idea: – We need an implication, which means we have to do Imply Introduction – To do an imply introduction, we need to prove the sequent E(x) ⇒ E(x) ∨ ¬E(x) 8

– E(x) ∨ ¬E(x) can be shown just by assuming either E(x) or ¬E(x) to be true • Proof – Assume E(p), p is an arbitrary value – By Or introduction, we have E(p) E(p) ∨ ¬E(p) – This sequent doesn’t rely on any more assumptions, and in particular, we can discharge the E(x) assumption – By Introduce Implication, we have E(p) ⇒ E(p) ∨ ¬E(p) – Since p is arbitrary, by introduce forall, we have ∀x.E(x) ⇒ E(x) ∨ ¬E(x) 4.2.4 Anti-Example: All natural numbers are even

• Let E(x) mean that x is even • E(2) ∀x.E(x) [WRONG]

• Problem is that we didn’t show that it works for an arbitrary natural number; we just showed that it works for a particular one.

4.3

4.3.1

Universal Elimination

Deﬁnition F (p)

• ∀x.F (x)

• If you have established a property for everything in the universe, you can assume it holds for a particular element of the universe. 4.3.2 Example: F (p), ∀x.F (x) ⇒ G(x) G(p) F (p) where p is the same variable as in F (p)

• By forall elimination, ∀x.F (x) ⇒ G(x) • Now we have F (p), F (p) ⇒ G(p) • By Modus Ponens, we have G(p) 4.3.3

Example: ∀x.F (x) ⇒ G(x), ∀x.G(x) ⇒ H(x)

∀x.F (x) ⇒ H(x)

• By forall elimination, F (p) ⇒ G(p) for an arbitrary p • By forall elimination, G(p) ⇒ H(p) • By implication chain, F (p) ⇒ G(p), G(p) ⇒ H(p) F (p) ⇒ H(p)

• Since this is for an arbitrary p, we can use forall introduction to get ∀x.F (x) ⇒ G(x), ∀x.G(x) ⇒ H(x) ∀x.F (x) ⇒ H(x)

9

4.3.4

Example: ∀x.∀y.F (x, y)

∀y.∀x.F (x, y)

• By forall elimination, we have ∀y.F (p, y) where p is arbitrary • By forall elimination, we have F (p, q) where q is arbitrary • By forall introduction, we have ∀x.F (x, q) • By forall introduction, we have ∀y.∀x.F (x, q) • So, we have just shown that the order of forall quantiﬁers does not matter. 4.3.5 Example: ∀x.P ⇒ f (x) P ⇒ ∀x.f (x) P ⇒ f (c), c is arbitrary

• By forall elimination, we have ∀x.P ⇒ f (x) • Assume P. Then, we have P, P ⇒ f (c) • By modus ponens, we have f (c). • By forall introduction, we have ∀x.f (x)

• By introduce implication, we have P ⇒ ∀x.f (x) 4.3.6 Exercise 9: Prove ∀x.F (x), ∀x.F (x) ⇒ G(x) ∀xG(x)

• By forall elimination, we have F (c), c is arbitrary. • By forall elimination, we have F (c) ⇒ G(c) • By modus ponens on F (c), F (c) ⇒ G(c), we have G(c) • Since c was arbitrary, we can introduce forall to get ∀x.G(x)

4.4

4.4.1

Existential Introduction

Deﬁnition

• If f (p) has been established for a particular p, then you can infer ∃p.f (p) 4.4.2 Example: ∀x.F (x) ∃x.F (x)

• By forall elimination, we have F (c) for an arbitrary c • By exists introduction, we have ∃x.F (x)

10

4.5

4.5.1

Existential Elimination

Deﬁnition

• Recall or elimination: – If you have a ∨ c, and a – This was proof by cases • Existential Elimination is a generalization of this idea • If you have ∃x.F (x), F (c) 4.5.2 A{carbitrary} then you can infer A ∃x.Q(x) c and b c then you have c

Example: ∃x.P (x), ∀x.P (x) ⇒ Q(x)

• By forall elimination, we have P (c) ⇒ Q(c), c is arbitrary. • Assume P (c). This is allowed because we have ∃x, P (x) • By modus ponens on P (c), P (c) ⇒ Q(c), we have Q(c). • By existential introduction on Q(c), we have ∃x.Q(x) 4.5.3 Example: ∃x.∀yF (x, y) ∀y.∃x.F (x, y)

• By forall elimination on ∀yF (x, y), we have F (x, q), q arbitrary • So we have ∃x.F (x, q) • By forall introduction, we have ∀y∃x.F (x, y) 4.5.4 Exercise 10: Prove ∃x.∃y.F (x, y) ∃y.∃x.F (x, y)

• Assume F (a, b). This is allowed because there must be atleast one a and one b for which F holds. • By existential elimination, we have ∃y.F (a, y), a arbitrary • By existential elimination, we have F (a, b), b arbitrary • By existential introduction, we have ∃x.F (x, b) • By existential introduction, we have ∃y, ∃x.F (x, y) • (This proof might be incorrect)

11

4.5.5

Exercise 11: Find a counterexample for: ∀y, ∃x.F (x, y)

∃x.∀yF (x, y)

• Let F (x, y) mean that x is greater than y • Suppose the universe is the natural numbers • Then, ∀y, ∃x.F (x, y) says that the natural numbers is unbounded, which is correct • But, ∃x.∀y.F (x, y) says that there is some natural number that is larger than all others, which is incorrect. 4.5.6 Exercise 12: Prove: ∀x, (F (x) ∧ G(x)) (∀xF (x)) ∧ (∀x.G(x))

• By forall elimination, we have F (c) ∧ G(c), c arbitrary • By and elimination, we have F (c) as well as G(c) • By forall introduction, we have ∀x.F (x) as well as ∀x.G(x) • By and introduction, we have (∀xF (x)) ∧ (∀x.G(x))

5

5.1

**Algebraic Laws of Predicate Logic
**

Law: Introducing and removing quantiﬁers

• ∀x.f (x) ⇒ f (c) • f (c) ⇒ ∃x.f (x) • Note that these are implications and only work in one direction

5.2

Example: ∀x.f (x) ⇒ ∃x.f (x)

• ∀x.f (x) • f (c), for arbitrary c • ∃x.f (x)

5.3

Law: Quantiﬁers and Negations

• ∀x.¬f (x) = ¬(∃x.f (x)) • ∃x.¬f (x) = ¬(∀x.f (x))

12

5.4

Law: Combining Propositions

• In all of the following, q does not contain x as a variable • (∀x.f (x)) ∧ q = ∀x(f (x) ∧ q) • (∀x.f (x)) ∨ q = ∀x(f (x) ∨ q) • (∃x.f (x)) ∧ q = ∃x.(f (x) ∧ q) • (∃x.f (x)) ∨ q = ∃x.(f (x) ∨ q) • Summary: we can push in propositions inside quantiﬁers if they don’t have the quantiﬁed variable

5.5

Laws: Combining Quantiﬁers

• ∀x.f (x) ∧ ∀x.g(x) = ∀x(f (x) ∧ g(x)) • ∀x.f (x) ∨ ∀x.g(x) ⇒ f orallx(f (x) ∨ g(x)) – we’re going from a strong statement to a weak one – Strong statement: both properties f and g hold for all x – Weak statement: atleast one of f and g hold for all x • ∃x.(f (x) ∨ g(x)) ⇒ ∃x.f (x) ∧ ∃x.g(x) – Also going from strong to weak – Strong: there’s atleast one element which has both properties f and g – Weak: there is atleast one element which has f , and atleast one which has g. The two elements don’t have to be the same. • ∃x.f (x) ∨ ∃x.g(x) = ∃x.(f (x) ∨ g(x))

5.6

Example: ∀x.(f (x) ∧ ¬g(x)) = ∀x.f (x) ∧ ¬∃.g(x)

• Direct proof starting from the left side • ∀x.(f (x) ∧ ¬g(x)) • (∀x.f (x)) ∧ (∀x.¬g(x)) • (∀x.f (x)) ∧ ¬(∃x.g(x))

13

5.7

Example: ∃x.(f (x) ⇒ g(x)) ∧ (∀x.f (x)) ⇒ ∃x.g(x)

• Direct proof starting from the left side • First, rename variable to get ∀y.f (y) • Now, push the forall inside the exists to get ∃x.((f (x) ⇒ g(x)) ∧ ∀y.f (y)) • Remove the forall to get: ∃x.((f (x) ⇒ g(x)) ∧ f (x)) • Use modus ponens to get ∃x.g(x)

6

Further Reading

• See references at end of chapter 6 • Mathematical Writing by Knuth, larrabee, and Roberts • Proofs from THE BOOK by Aigner and Ziegler

7

7.1

Review Exercises

Exercise 13

Problem

7.1.1

• Universe has 10 elements • Expression: ∀x.∃y.∀zF (x, y, z) • want to express it in a quantiﬁer free form. 7.1.2 How many times will F occur in that form?

• Eliminating ∀z, we have this innermost expression: F (x, y, n1 ) ∧ F (x, y, n2 ) ∧ · · · ∧ F (x, y, n1 0) • This has 10 items • Eliminating the ∃y replaces F (x, y, n1 ) with F (x, n1 , n1 ) ∨ F (x, n2 , n1 ) ∨ · · · ∨ F (x, n1 0, n1 ) • So, 10 terms per term from before. (Total: 100) • Eliminating the ∀x replaces each F (x, n1 , n1 ) with F (n1 , n1 , n1 ) ∨ F (n2 , n1 , n1 ) ∨ · · · ∨ F (n1 0, n1 , n1 ) • So, 10 terms per term from before. (Total: 1000) • In general, we have N k terms where N is size of universe, k is the number of quantiﬁers we’re removing

14

7.2

Exercise 14: Prove (∃f (x)) ∨ (∃g(x))

∃x.(f (x) ∧ g(x))

• By exists elimination, we get f (c) for some c • By exists elimination, we get g(d) for some d • By or introduction, we get f (c) ∨ g(d) • By exists introduction, we get ∃x.(f (x) ∨ g(d)) • By exists introduction, we get ∃y∃x.(f (x) ∨ g(y)) • Since the existence of either x or y makes the whole statement true, we can combine them to get ∃x.f (x) ∨ g(x)

7.3

Exercise 15: Prove (∀x.f (x)) ∨ (∀x.g(x))

∀x(f (x) ∨ g(x))

• By forall elimination, we get f (c) for arbitrary c • By forall elimination, we get g(c) • By or introduction, we have f (c) ∨ g(c) • Since the above holds true for arbitrary c, by universal introduction, ∀x.(f (x) ∨ g(x))

7.4

**Exercise 16: Prove converse of Theorem 63
**

P ⇒ ∀x.f (x) ∀x.P ⇒ f (x)

• Theorem 63: ∀x.P ⇒ f (x)

• The converse of this is: P ⇒ ∀x.f (x)

• Assume P . Then by modus ponens on P, P ⇒ ∀x.f (x), we have ∀x.f (x) • By forall elimination, we have f (c) • By implies introduction, we have P ⇒ f (c) • By forall introduction, we have ∀x.P ⇒ f (x)

7.5

Exercise 17: Provide Counterexamples

• In “combining quantiﬁers”, we had two laws that were implications not equalities. • Provide counterexamples that show why the laws don’t hold in the opposite direction • Counterexample for ∀x.(f (x) ∨ g(x)) ⇒ ∀x.f (x) ∨ ∀x.g(x)) – Suppose f (x) means x is even – Suppose g(x) means x is odd – Universe is natural numbers. – Then, left side is true because every number is either even or odd 15

– But on the right side we also claim that every number is even, and every number is odd. Both of which are false. • More concrete counterexample: – Universe is: {Shrek, Donkey} – f (x) means x = Shrek – g(x) means x = Donkey – Left Side: – ∀x.(f (x) ∨ g(x)) – (f (Shrek) ∨ g(Shrek)) ∧ (f (Donkey) ∨ g(Donkey)) – (T rue ∨ F alse) ∧ (F alse ∨ T rue) – T rue – Right Side: – (∀x.f (x)) ∨ (∀x.g(x)) – (f (Shrek) ∧ f (Donkey)) ∨ (g(Shrek) ∧ g(Donkey)) – (T rue ∧ F alse) ∨ (F alse ∧ T rue) – F alse ∨ F alse = F alse – So, we’re trying to do a T rue ⇒ F alse, which is F alse • Counterexample for ∃x.f (x) ∧ ∃x.g(x) ⇒ ∃x.(f (x) ∧ g(x)) – Again using the Shrek, Donkey example – Left side: – ∃x.f (x) ∧ ∃x.g(x) – (f (Shrek) ∨ f (Donkey)) ∧ (g(Shrek) ∨ g(Donkey)) – (T rue ∨ F alse) ∧ (F alse ∨ T rue) – T rue – Right side: – ∃x.(f (x) ∧ g(x)) – (f (Shrek) ∧ g(Shrek)) ∨ (f (Donkey) ∧ g(Donkey)) – (T rue ∧ F alse) ∨ (F alse ∧ T rue) – F alse ∨ F alse – F alse – So, we’re trying to do a T rue ⇒ F alse, which is F alse

7.6

TODO : Exercise 18: Prove (∀x.f (x) ⇒ h(x) ∧ ∀x.g(x) ⇒ h(x)) ⇒ ∀x.(f (x) ∨ g(x) ⇒ h(x))

• By using the laws on combining quantiﬁers, we can get ∀x.((f (x) ⇒ h(x))∧(g(x) ⇒ h(x)) • TODO: Now we need to do some kind of or elimination and combine. 16

7.7

Exercise 19

• Universe is natural numbers • predicate: “if a number occurs in either of the sequences that are arguments to append, it occurs in the ﬁnal series as well” • (The proof is easy by induction, but they want something else)

17

- asmt8ans
- Series
- Madhavan Logic
- Akrab Bersama Sandi Matematika
- Number and proof
- 1. Functions
- Algumas Soluções Cap4 Stein
- AnalysisBH_HW1
- analisefuncionalexercicios
- An Integer as a Sum of Consecutive Integers
- Partial Fraction Expansions for Newton's and Halley's Iterations for Square Roots
- Hahn-Banach theorems
- ComplexNumbers and Euler Formulas
- FLT2
- 20_3
- ExtraExamples_1_6
- Number Theory
- Gs2014 Qp Mth
- DM
- mth202
- sdarticle
- espaço m
- Exam 1 Practice Solutions
- hmw4
- M340L True False - Copy
- Bo de Bertrand
- primroot2
- W. D. Joyner - Mathematics of the Rubik
- Tutorial 3 So Lns

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue listening from where you left off, or restart the preview.

scribd